2021
DOI: 10.1371/journal.pone.0256516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of government policies and the Nowruz holidays on confirmed COVID-19 cases in Iran: An intervention time series analysis

Abstract: Background Public health policies with varying degrees of restriction have been imposed around the world to prevent the spread of coronavirus disease 2019 (COVID-19). In this study, we aimed to evaluate the effects of the implementation of government policies and the Nowruz holidays on the containment of the COVID-19 pandemic in Iran, using an intervention time series analysis. Methods Daily data on COVID-19 cases registered between February 19 and May 2, 2020 were collected from the World Health Organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(30 reference statements)
3
3
0
Order By: Relevance
“…This expected time is directly related to the period of manifestation of symptoms and/or the results of the exam performed. Another study, carried out by Hadianfar et al, [21] also agrees with the results found, where an approximate increase of up to 1,872 new cases was observed after holidays (p<0.001).…”
Section: Discussionsupporting
confidence: 85%
“…This expected time is directly related to the period of manifestation of symptoms and/or the results of the exam performed. Another study, carried out by Hadianfar et al, [21] also agrees with the results found, where an approximate increase of up to 1,872 new cases was observed after holidays (p<0.001).…”
Section: Discussionsupporting
confidence: 85%
“…This expected time is directly related to the period of manifestation of symptoms and/or the results of the exam performed. Another study, carried out by Hadianfar et al [21] also agrees with the results found, where an approximate increase of up to 1872 new cases was observed after holidays (p < 0.001).…”
Section: Discussionsupporting
confidence: 83%
“…This is in agreement with another study showing that social distancing implemented in 28 European countries decreased daily COVID-19 cases growth rate from 24% to less than 2% [39]. A research on the social distancing order in Iran revealed that it could significantly decrease new cases by an average of 2128 per day [8]. How the strategy is implemented and how strictly it is enforced is more important than the specific strategy chosen to combat the pandemic.…”
Section: Plos Onesupporting
confidence: 89%
“…Each country implemented different policies to suppress the pandemic like closing schools and universities in Iran, Zambia [8][9][10], prohibiting restaurant dine-in services in US and Brazil [11][12][13], closing gyms in Saudi Arabia and US [14,15], ban travelers in Europe and US [16][17][18][19] and total or partial lockdowns to completely prevent any contact between people in France, Germany, Italy, Russia, Denmark and many other countries [20,21]. Furthermore, implementing some strategies has economical and mental costs [22,23].…”
Section: Introductionmentioning
confidence: 99%